2017
DOI: 10.1002/ange.201703700
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Dependence of the Rates of Reaction of Trifluoroacetic Acid with Criegee Intermediates

Abstract: Abstract:The rate coefficients for gas-phase reaction of trifluoroacetic acid (TFA) with two Criegee intermediates, formaldehyde oxide and acetone oxide,decrease with increasing temperature in the range 240-340 K. The rate coefficients k(CH 2 OO + CF 3 COOH) = (3.4 AE 0. Halogenated organic acids such as trifluoroacetic acid (TFA) form in the Earthst roposphere by oxidation of anthropogenically produced hydrofluorocarbons (HFCs), hydrochlorofluorocarbons (HCFCs) and hydrofluoro-olefins (HFOs), [1] and also hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…The high concentrations of CH 3 COOH in the Amazon rain forest area coincide with high concentrations of sCI, and their reactions could significantly reduce the atmospheric concentration of CH 3 COOH. Chhantyal‐Pun et al () found that these reactions show a relatively small temperature dependence over the temperature range found in the lower troposphere. Incorporating these reactions of Criegee intermediates with CH 3 COOH in the model results in reduction of CH 3 COOH in the Amazon rain forest area.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high concentrations of CH 3 COOH in the Amazon rain forest area coincide with high concentrations of sCI, and their reactions could significantly reduce the atmospheric concentration of CH 3 COOH. Chhantyal‐Pun et al () found that these reactions show a relatively small temperature dependence over the temperature range found in the lower troposphere. Incorporating these reactions of Criegee intermediates with CH 3 COOH in the model results in reduction of CH 3 COOH in the Amazon rain forest area.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggested that the reaction of Criegee intermediates with organic acids may be of importance for the tropospheric chemistry of CH 3 COOH (Chhantyal‐Pun et al, ; Welz et al, ). An effort has been made to establish the scale of the potential contribution of these reactions to the tropospheric levels of CH 3 COOH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] Recent laboratory studies showed that their reactions with certain carboxylic acids approach or exceed the gas-kinetic collisional limit. [15][16] Complementary global modelling studies indicated that inclusion of these reactions in chemical schemes significantly lowers the predicted lifetimes and steady state concentrations of these acids in the troposphere. [15][16] The wide range of biogenic and anthropogenic carboxylic acids emitted to the troposphere, and the variety of Criegee intermediates produced by ozonolysis of alkenes (including isoprene and terpenes), mean there are many possible combinations of reactions of atmospheric Criegee intermediates and carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16] Complementary global modelling studies indicated that inclusion of these reactions in chemical schemes significantly lowers the predicted lifetimes and steady state concentrations of these acids in the troposphere. [15][16] The wide range of biogenic and anthropogenic carboxylic acids emitted to the troposphere, and the variety of Criegee intermediates produced by ozonolysis of alkenes (including isoprene and terpenes), mean there are many possible combinations of reactions of atmospheric Criegee intermediates and carboxylic acids. This complexity necessitates development of structure-activity relationships (SARs) to account fully for the suite of reaction rates in atmospheric chemistry models.…”
Section: Introductionmentioning
confidence: 99%